2018
DOI: 10.1186/s13229-018-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Chr16p11.2 ASD candidate gene QPRT leads to aberrant neuronal differentiation in the SH-SY5Y neuronal cell model

Abstract: BackgroundAltered neuronal development is discussed as the underlying pathogenic mechanism of autism spectrum disorders (ASD). Copy number variations of 16p11.2 have recurrently been identified in individuals with ASD. Of the 29 genes within this region, quinolinate phosphoribosyltransferase (QPRT) showed the strongest regulation during neuronal differentiation of SH-SY5Y neuroblastoma cells. We hypothesized a causal relation between this tryptophan metabolism-related enzyme and neuronal differentiation. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 76 publications
(93 reference statements)
0
34
0
1
Order By: Relevance
“…In this context, it should be noticed that quinolinate phosphoribosyltransferase (QPRT), which belongs to the phosphoribosyltransferase family and is involved in de novo NAD biosynthesis using quinolinic acid (QA) as a precursor in both prokaryotes and eukaryotes, has not been thoroughly investigated in the context of cancer and inflammation, but there are evidences that also this enzyme might play a role (Hinsch et al, 2009;Sahm et al, 2013;Ullmark et al, 2017;Haslinger et al, 2018).…”
Section: Naprt Is An Important Counterpart To Nampt In Nad Metabolismmentioning
confidence: 99%
“…In this context, it should be noticed that quinolinate phosphoribosyltransferase (QPRT), which belongs to the phosphoribosyltransferase family and is involved in de novo NAD biosynthesis using quinolinic acid (QA) as a precursor in both prokaryotes and eukaryotes, has not been thoroughly investigated in the context of cancer and inflammation, but there are evidences that also this enzyme might play a role (Hinsch et al, 2009;Sahm et al, 2013;Ullmark et al, 2017;Haslinger et al, 2018).…”
Section: Naprt Is An Important Counterpart To Nampt In Nad Metabolismmentioning
confidence: 99%
“…Such abnormalities could affect tryptophan availability during brain development, indirectly altering serotonin and KP activity. Furthermore, the tryptophan metabolism-related enzyme quinolinate phosphoribosyl-transferase (QPRT) affects the regulation of genes and gene networks previously implicated in ASDs [ 154 ] and, at the same time, a deletion in 16p11.2, the chromosomal regions responsible for QPRT codification, has strongly been associated to ASD [ 154 ].…”
Section: The Kynurenines Pathwaymentioning
confidence: 99%
“…In the de novo pathway, tryptophan is first converted to quinolinic acid (QA) through a series of steps; QA is converted to nicotinic acid mononucleotide (NAMN) via quinolinate phosphoribosyltransferase (QPRT) and is then converted to NAD + via nicotinamide nucleotide adenylyltransferase (NMNAT) and NAD synthetase (NADS). In normal cells, QPRT expression follows a tissue-specific distribution; more recent insights have revealed that QPRT expression is altered in some cancer cells (4)(5)(6)(7). The Preiss-Handler pathway converts nicotinic acid (NA) to NAMN through nicotinate phosphoribosyltransferase (NAPRT), an enzyme that is widely expressed in normal tissues but variably expressed in cancer cells (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%